Method of coding resource blocks for 5G technology - Бараннік, В.В.; Окладний, Д.Е.; Бараннік, Д.В. (Science-based technologies, 2018)
The structure of the LTE radio frame has been analyzed for the use of a fundamentally new coding method. The optimal structural unit of LTE - radio frame - resource block is found and restructured. The resource block was divided into three-bit streams in order to use small bit code words; the bit width of the code words was reduced to achieve the possibility of data transfer using inverse cosine transform on radio communication channels. The process of encoding a resource block is described. A mathematical apparatus for software modeling of the encoding process of a resource block has been developed. The statistical parameters for reducing the bit intensity of the transformed data stream with the help of systems with non-uniform weight coefficients are calculated. A significant decrease in the bit rate of the information stream in the LTE radio frame has been achieved due to a new method of coding resource blocks.